2012
DOI: 10.1021/es3025726
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Reduction of Fe(II)EDTA-NO/Fe(III)EDTA in NOx Scrubber Solution Using a Three-Dimensional Biofilm-Electrode Reactor

Abstract: A promising technique called chemical absorption-biological reduction (CABR) integrated approach has been developed recently for the nitrogen oxides (NO(x)) removal from flue gases. The major challenge for this approach is how to enhance the rate of the biological reduction step. To tackle the challenge, a three-dimensional biofilm-electrode reactor (3D-BER) was utilized. This reactor provides not only considerable amount of sites for biofilm, but also many electron donors for bioreduction. Factors affecting t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
17
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 38 publications
(17 citation statements)
references
References 29 publications
0
17
0
Order By: Relevance
“…It has been demonstrated that the CABR process features higher NO removal efficiency compared to the conventional biological denitrification, which showed over 90% in the long term operation under the typical CABR conditions . Parametric tests revealed that the gas residence time and the concentration of Fe­(II)­EDTA were critical to achieve a high NO removal efficiency. It has been confirmed that the main end product of the NO reduction in the CABR system was nitrogen gas while N 2 O was an intermediate . Batch experimental results showed that the Fe­(III)­EDTA reduction rate was the limitation to achieving high NO removal capacity …”
Section: Introductionmentioning
confidence: 95%
“…It has been demonstrated that the CABR process features higher NO removal efficiency compared to the conventional biological denitrification, which showed over 90% in the long term operation under the typical CABR conditions . Parametric tests revealed that the gas residence time and the concentration of Fe­(II)­EDTA were critical to achieve a high NO removal efficiency. It has been confirmed that the main end product of the NO reduction in the CABR system was nitrogen gas while N 2 O was an intermediate . Batch experimental results showed that the Fe­(III)­EDTA reduction rate was the limitation to achieving high NO removal capacity …”
Section: Introductionmentioning
confidence: 95%
“…NO x , a typical component in flue gas streams, is recognized as another main pollutant that induces acid rain and greenhouse effects. , Compared with the various denitrification technologies, the liquid-phase denitrification characterized by Fe­(II)­EDTA has been demonstrated as a very promising research direction in controlling NO x emission because of its speedy capture ability for NO x . , However, the easy conversion of Fe­(II)­EDTA to Fe­(III)­EDTA causing a poor ability to absorb NO x and the regeneration of Fe­(II)­EDTA after absorbing NO have significantly restricted the large-scale application of the Fe­(II)­EDTA-based liquid-phase denitrification technique. In most studies, the simultaneous reductions of Fe­(II)­EDTA-NO and Fe­(III)­EDTA mainly focused on biological reduction.…”
Section: Introductionmentioning
confidence: 99%
“…The main reactions involved in the chemical absorption–biological reduction can be expressed as Surprisingly, Fe II (EDTA) and Fe III (EDTA) may be directly involved in the nitric oxide reductase (NOR) reduction during denitrification, based on the available midpoint potential between NO reductases and Fe II (EDTA)/Fe III (EDTA) system . However, according to some studies on biofilm-electrode reactors, Fe II (EDTA) is directly involved in the microbial reduction of chelate Fe II (EDTA)-NO as a dominant electron donor …”
Section: Introductionmentioning
confidence: 99%